How the Experience of Living Overseas Sharpened Indonesian Student’s Intercultural Communication Competence Through Student Exchange Program at the University of Pécs - Kanaya Faza, Kayla; Lukmantoro, Triyono; Manalu, Rouli (Interaksi Online, 2024)
This study delves into the intercultural communication competence of Indonesian students participating in the Exchange Student Program at the University of Pécs. It examines how they navigate the substantial cultural differences between Hungary and Indonesia, employing Byram's (1997) five elements of intercultural communication competence—attitude, knowledge, skills of interpreting and relating, skills of discovery and interaction, and critical cultural awareness/political education—and intergroup contact theory to explore potential prejudice. The findings reveal that despite facing significant cultural challenges, the students demonstrate and substantially enhance their intercultural communication competence. Utilizing a phenomenological approach, the intellectual perspectives of each student in navigating cultural differences enrich the study, contributing to a deeper understanding of their intercultural experiences and offering insights into broader cultural adaptation in educational exchange programs. All Indonesian students in this study exhibit their intercultural communication competence.